The determinants of national savings in Algeria A macro-econometric investigation for the period 1994-2009 - Berrehouma, Abdelhamid (Sciences humaines; Vol. 29 (2013): SCIENCES HUMAINES, 2014)
يهدف هذا المقال إلى توضيح الدور الذي لعبه الادخار الوطني في الجزائر في تمويل البرامج الاستثمارية خلال الفترة 1994 إلى 2009، و ذلك من خلال إجراء دراسة قياسية لتحديد أي المتغيرات الاقتصادية التي كان لها تأثير مباشر على الادخار الوطني، والتنبؤ بمستوياته خلال المخطط الخماسي الثاني والذي يغطي الفترة من 2010 إلى 2014.  نتائج هذه الدراسة ستمكننا من معرفة أي السياسات الاقتصادية الواجب استخدامها مستقبلا من فبل الحكومة الجزائرية لجمع وتعبئة الادخار الوطني أكثر لتمويل البرامج الاستثمارية المدرجة في المخطط الخماسي الثاني. الكلمات المفتاحية: الادخار الوطني، البرامج الاستثمارية، المحددات، التنبؤ.   This paper aims to investigate the relevant role of national savings in Algeria to finance the investment programs during the period (1994-2009), using the appropriate econometric methods to determine the crucial factors that have effects on Algerian National Savings, and predict the future behaviors of this variable, especially for the Second Five-Year Development Plan 2010-2014. The results of this study enable us to determine the policies should be applied by the Algerian Government for more collection and mobilization of national savings to finance the investment programs for the period of the Second Five-Year Development Plan. Passwords : National savings, investment’s programs, determinants, prediction.